Evaluation of Major Soil Nutrients After the Application of Microbial-Inoculated Acidified Biochar Pellets Using a Sigmoid Function - JooHee Nam; JoungDu Shin; Jae-Yee Choi; SangWon Park; JaeWook Chung; Changyoon Jeong (Agronomy, 2025)
This experiment aimed to investigate nutrient dynamics in soil and compare plant growth responses after treatment with acidified biochar pellets inoculated with microorganisms during Kimchi cabbage cultivation, using a sigmoid function model. The treatments included the following: Control–only guano application; ABPM 27 (Pseudomonas fluorescens 22BCO027); and ABPM 86 (Bacillus megaterium 22BCO086). Guano and biochar pellets were applied at 320 kg ha−1, based on the recommended nitrogen application rate for cabbage cultivation. The results showed that the cumulative NO3-N and P2O5 in the ABPM 27 treatment were 27.7% and 12.1% higher, respectively, compared with the control. The maximum cumulative K was not significantly different (p > 0.05) between the treatments. The cumulative NH4-N and NO3-N were well fitted (R2 > 0.824) to the sigmoid curves, while the cumulative P2O5 and K were well described with the linear function (R2 > 0.970) regardless of treatment. The highest yield was 77.4 tonnes ha−1 under the ABPM 27 treatment. Therefore, the ABPM 27 treatment is strongly recommended for enhancing cabbage yield in organic farming due to its high capacity for accumulating NO3-N and P2O5.